Don't forget to look down – collaborative approaches to predator conservation. (24th March 2017) - Redpath, Steve M.; Linnell, John D. C.; Festa‐Bianchet, Marco; Boitani, Luigi; Bunnefeld, Nils; Dickman, Amy; Gutiérrez, R. J.; Irvine, R. J.; Johansson, Maria; Majić, Aleksandra; McMahon, Barry J.; Pooley, Simon; et al.
ABSTRACT: Finding effective ways of conserving large carnivores is widely recognised as a priority in conservation. However, there is disagreement about the most effective way to do this, with some favouring top‐down 'command and control' approaches and others favouring collaboration. Arguments for coercive top‐down approaches have been presented elsewhere; here we present arguments for collaboration. In many parts of the developed world, flexibility of approach is built into the legislation, so that conservation objectives are balanced with other legitimate goals. In the developing world, limited resources, poverty and weak governance mean that collaborative approaches are likely to play a particularly important part in carnivore conservation. In general, coercive policies may lead to the deterioration of political legitimacy and potentially to non‐compliance issues such as illegal killing, whereas collaborative approaches may lead to psychological ownership, enhanced trust, learning, and better social outcomes. Sustainable hunting/trapping plays a crucial part in the conservation and management of many large carnivores. There are many different models for how to conserve carnivores effectively across the world, research is now required to reduce uncertainty and examine the effectiveness of these approaches in different contexts. Abstract : Related Content